The The Effect of Local Wisdom-Based Problem-Based Learning on Students’ Entrepreneurial Spirit in Entrepreneurship Learning at SMA Negeri 1 Karangkobar - Wiwid Eka Yuni Setiyani; Indri Murniawaty (UM Purwokerto Press, 2026)
The primary objective of this study was to determine whether Local Wisdom-Based Problem-Based Learning (PBL) significantly affects students' entrepreneurial spirit within entrepreneurship instruction at SMA Negeri 1 Karangkobar. It was hypothesized that embedding local wisdom into the PBL approach would generate meaningful learning experiences capable of enhancing students' critical thinking, creativity, problem-solving competence, and entrepreneurial spirit through contextually grounded instruction. To this end, a quantitative, associative research design was employed, drawing on a total sample of 45 eleventh-grade students from classes XI E and The analysis confirmed a positive and significant effect of Local Wisdom-Based Problem-Based Learning on entrepreneurial spirit (significance value = 0.023, p < 0.05), represented by the regression equation Y = 19.870 + 0.406X. The determination coefficient (R² = 0.115) further indicated that the model explained 11.5% of the variance in entrepreneurial spirit, with the remaining 88.5% attributable to unexamined external factors. Collectively, these findings point to the potential of integrating local wisdom into Problem-Based Learning as an effective instructional strategy for nurturing entrepreneurial spirit among senior high school students.